Effect of normal load and roughness on the nanoscale friction coefficient in the elastic and plastic contact regime - Kumar, Aditya; Staedler, Thorsten; Jiang, Xin (Beilstein Journal of Nanotechnology, 2013)
The influence of applied normal load and roughness on the tribological behavior between the indenter and sample surface during nanoindentation-based scratching has been experimentally investigated by using different surfaces (fused silica and diamond-like carbon) featuring various degrees of roughness. At a sufficiently low applied normal load, wherein the contact is elastic, the friction coefficient is constant. However, at increased normal loads the contact involves plastic deformation and the friction coefficient increases with increasing normal load. The critical load range for a transition from predominantly elastic to plastic contact, between the indenter and sample surface, increases with increasing size of indenter and decreases with roughness. Distinct differences between the present experimental results and the existing theoretical models/predictions are discussed.
Keywords: nanoindentation; nanotribology; scratch testing; surface roughness